Genomics of Acute Myeloid Leukemia: The Next Generation - Riva, Laura; Luzi, Lucilla; Pelicci, Pier Giuseppe (Frontiers in Oncology, 2012)
Acute myeloid leukemia (AML) is, as other types of cancer, a genetic disorder of somatic cells. The detection of somatic molecular abnormalities that may cause and maintain AML is crucial for patient stratification. The development of mutation-specific therapeutic interventions will hopefully increase cure rates and improve patients’ quality of life. This review illustrates how next generation sequencing technologies are changing the study of cancer genomics of adult AML patients.